Essays on health and the environment in Brazil - Rozenfeld, Tales (2021)
As climate changes, scientists expect that some parts of the earth will experience a growth in the frequency and intensity of droughts. This doctoral dissertation consists of two studies exploring possible health issues that might arise from an increase in water scarcity. In the first study, we investigate the effects of abrupt measures implemented by the water company of the Metropolitan Region of São Paulo to cope with an unexpected drought that affected the region during 2014 and 2015. Even though the company manages a robust water and sanitation system, the severity of the drought drove the local water supply services to the brink of a collapse, and a series of strict measures had to be implemented to guarantee the supply to the population. During this drought, an important measure was to reduce the water pressure within the distribution network to avoid losses through leakage points. Our analysis suggests that, although important, this policy had the unexpected consequence of increasing the hospitalization by fecal-oral transmitted diseases. Consistent with the literature, we find evidence that the low-income children and elderly were the most affected groups. Analyzing variations in bottled water prices, we also find evidence that the population engaged with defensive behaviors against the water supply issues, which seems to have influenced the observed health outcomes. In the second study from this dissertation, we discuss another consequence of water scarcity that arises in places that, like Brazil, rely on hydroelectric power plants to supply their energy demand. In these regions, a drought might shift the energy production toward a more intensive use of thermoelectric power. Mounting evidence suggests that this energy source has a negative impact on the health outcomes of the population, and coal-fueled power plants are usually at the center of discussion due to their high emission rates. Still, other types of thermoelectric power plants might also be harmful to the health of the surrounding population. In this work, we investigate if different types of thermoelectric power plants affect the health of the population living nearby. We find evidence that coal-fired power plants are the most harmful for health, increasing the infant mortality rate in nearby communities. Our findings also robustly suggest that female children are more affected than males, but the results are probably underestimated, since we also find evidence of fetal selection.